Method of producing modified carbon fiber-containing thermoplastic resin composition, and method of producing molding
By using hydroxide spherical silicone particles to modify carbon fibers, the dispersion and adhesion problems when carbon fibers are combined with thermoplastic resins are solved, and better mold forming performance and mechanical strength are achieved.
Patent Information
- Application Number
- JP2024213146
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the combination of carbon fiber and thermoplastic resin has problems such as poor dispersion of carbon fiber and poor resin fluidity, resulting in poor mold forming performance, and insufficient interface adhesion and mechanical strength between the thermoplastic resin and carbon fiber.
By using hydroxide spherical silicone particles as surface modification agents, the carbon fibers are modified to form improved mutual adhesion with the thermoplastic resin, thereby improving the dispersion and interface adhesion of the carbon fibers.
The uniform dispersion of carbon fiber in the thermoplastic resin is achieved, the interfacial adhesion and mold forming performance are improved, and the mechanical strength of the finished product is significantly improved.
Smart Images

Figure 2025038011000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a modified carbon fiber-containing thermoplastic resin composition comprising carbon fiber whose surface has been modified with hydrophobic spherical silica microparticles and a thermoplastic resin. [Background technology]
[0002] Resin molded products reinforced with carbon fiber are lightweight and strong, and are used in a wide range of fields, including home appliance housings, sports equipment, aircraft applications, and automotive applications. Conventional carbon fiber reinforced resin molded products were manufactured using thermosetting resins, such as epoxy resins, but are being replaced by thermoplastic resins due to the complexity of manufacturing and recyclability. Furthermore, when chopped carbon fiber is mixed with thermoplastic resin, the dispersion of carbon fiber is poor, resulting in poor resin flow and moldability problems. Therefore, it has been proposed to treat the carbon fiber surface with various sizing agents (bundling agents) to improve dispersibility (see Patent Documents 1 and 2). In addition, when manufacturing a sheet-shaped product, it is common to prepare a prepreg and heat-press it into layers, and the interface adhesion during this process becomes a problem. It has also been proposed to add plate-shaped particles for the purpose of improving the interface adhesion (see Patent Documents 3 and 4). However, in either case, thermoplastic resins are inferior to thermosetting resins in terms of interface adhesion and mechanical strength.
[0003] Furthermore, polyolefin and polymethacrylic acid block copolymers (see Patent Document 5) and terpene resins (see Patent Document 6) have been proposed as compatibilizers for thermoplastic resins and carbon fibers treated with a sizing agent, but the improvement in mechanical strength was not satisfactory. Furthermore, methods have been proposed in which carbon fibers are treated with a dispersion liquid in which silicone rubber microparticles are dispersed in water using a cationic surfactant, and in which ethylene-vinyl acetate copolymer microparticles are dispersed in water using an anionic surfactant (see Patent Documents 7 and 8). However, these methods require prior electrolytic oxidation treatment of the carbon fibers, and involve complicated processes such as drying after dispersion treatment, and the mechanical strength and adhesion are still insufficient. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4094546 [Patent Document 2] JP 2017-14628 A [Patent Document 3] JP 2016-97558 A [Patent Document 4] JP 2011-213991 A [Patent Document 5] JP 2018-145245 A [Patent Document 6] JP 2019-182940 A [Patent Document 7] Patent No. 3193534 [Patent Document 8] Patent No. 3232169 Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, an object of the present invention is to provide a modified carbon fiber-containing thermoplastic resin composition using modified carbon fiber having improved affinity and adhesion to a thermoplastic resin matrix, and a method for producing a molded article thereof. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the inventors have discovered that the above problems can be solved by adding specific hydrophobic spherical silica microparticles to carbon fibers, and have completed the present invention.
[0007] That is, the present invention is as follows. <1> (A1) a step of obtaining hydrophilic spherical silica microparticles substantially composed of SiO units by hydrolyzing and condensing a tetrafunctional silane compound, a partial hydrolysis and condensation product thereof, or a mixture thereof; (A2) R is applied to the surface of the hydrophilic spherical silica fine particles. 1 SiO 3 / 2 Units (wherein R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms; (A3) The surface of the spherical silica particles obtained in the step (A2) is coated with R 2 3SiO 1 / 2 Units (wherein, each R 2 are the same or different and are substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms), A step A of producing hydrophobic spherical silica microparticles having a particle diameter in the range of 0.005 to 0.3 μm, a particle size distribution D90 / D10 value of 3 or less, an average circularity of 0.8 to 1, and a hydrophobicity of 50 or more by a method comprising the steps of: A step B of adding and mixing the hydrophobic spherical silica microparticles to carbon fibers having a length of 0.3 to 10 mm in an amount of at least 0.01% by mass based on the mass of the carbon fibers to produce modified carbon fibers; and A process C of adding 0.5 to 40 parts by mass of the modified carbon fiber to 100 parts by mass of a thermoplastic resin and mixing them. A method for producing a modified carbon fiber-containing thermoplastic resin composition comprising the steps of:
[0008] <2> The method for producing the hydrophobic spherical silica microparticles comprises: (A1) General formula (I): Si(OR 3 )4(I) (In the formula, each R 3are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms), a partial hydrolysis product thereof, or a mixture thereof is hydrolyzed and condensed in a mixed liquid of a hydrophilic organic solvent and water in the presence of a basic substance to obtain a mixed solvent dispersion of hydrophilic spherical silica fine particles substantially composed of SiO2 units, (A2) The obtained hydrophilic spherical silica microparticles are dispersed in a mixed solvent, and a compound having the general formula (II): R 1 Si(OR 4 )3(II) (In the formula, R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and each R 4 are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms), a partial hydrolysis product thereof, or a mixture thereof is added to treat the surface of the hydrophilic spherical silica fine particles, thereby forming a layer of R on the surface of the hydrophilic spherical silica fine particles. 1 SiO 3 / 2 Units (R 1 is as described above) to obtain a first dispersion of hydrophobic spherical silica microparticles in the mixed solvent, (A3) The obtained first hydrophobic spherical silica microparticles are dispersed in a mixed solvent, and a compound represented by the general formula (III): R 2 3SiNHSiR 2 3(III) (In the formula, each R 2 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms. Silazane compounds represented by the general formula (IV): R 2 3SiX (IV) (In the formula, R 2 is as defined in general formula (III), and X is an OH group or a hydrolyzable group), or a mixture thereof, to treat the surface of the first hydrophobic spherical silica fine particles with the compound, thereby forming a compound represented by R 2 3SiO 1 / 2 Units (R 2is as defined in general formula (III) to obtain second hydrophobic spherical silica microparticles, <1> A method for producing a modified carbon fiber-containing thermoplastic resin composition according to claim 1.
[0009] <3> Hydrophobic spherical silica microparticles are added and mixed in the range of 0.01 to 20.0 mass% relative to the carbon fibers. <1> or <2> A method for producing a modified carbon fiber-containing thermoplastic resin composition according to claim 1.
[0010] <4> The thermoplastic resin is at least one resin selected from the group consisting of polyolefin resins, polycarbonate resins, polyamide resins, and polyphenylene sulfide resins. <1> ~ <3> 13. A method for producing a modified carbon fiber-containing thermoplastic resin composition according to claim 12.
[0011] <5> <1> ~ <4> 2. A method for producing a molded article, comprising obtaining a modified carbon fiber-containing thermoplastic resin composition by the method according to any one of the above items 1 to 11, and hot molding the obtained modified carbon fiber-containing thermoplastic resin composition. Effect of the Invention
[0012] The modified carbon fiber-containing thermoplastic resin composition obtained by the manufacturing method of the present invention has excellent interfacial adhesion and moldability because the carbon fibers have been surface-modified with hydrophobic spherical silica microparticles, resulting in uniform dispersibility of the carbon fibers in the thermoplastic resin matrix. Furthermore, the molded article obtained by hot molding the modified carbon fiber-containing thermoplastic resin composition has excellent mechanical strength. Furthermore, the manufacturing method of the present invention does not include a step such as electrolytic oxidation treatment, and therefore the process is not complicated and is economical. [Brief description of the drawings]
[0013] [Figure 1] 1 is an electron microscope photograph of the modified carbon fiber obtained in Production Example 2. [Diagram 2] FIG. 2 is a schematic diagram showing a method for producing a molded sheet. [Diagram 3] FIG. 2 is a schematic diagram showing a method for preparing a fragmentation test piece. [Figure 4] FIG. 1 is a diagram showing a method for determining the critical fracture length and the interfacial shear strength from the measurement results of the tensile strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. <Carbon fiber component> The carbon fiber used in the present invention is not particularly limited, but examples thereof include polyacrylonitrile (PAN)-based, pitch-based carbon fibers made from petroleum tar or petroleum pitch, and cellulose-based carbon fibers made from viscose rayon, cellulose acetate, etc. Among these, PAN-based carbon fibers are preferred because of their excellent balance between strength and elastic modulus. The fiber length of the carbon fibers is not particularly limited, but from the standpoint of dispersibility in the thermoplastic resin matrix and strength, the fiber length is preferably 0.3 to 10 mm, and fibers of different lengths may be mixed and used.
[0015] The carbon fiber may be either untreated or surface-treated with a sizing agent to improve dispersibility. Specific examples of the sizing agent include at least one selected from the group consisting of epoxy resins, phenolic resins, urethane resins, polyester resins, and surfactant-containing resins.
[0016] <Hydrophobic spherical silica particles> (Step A) The characteristics of the hydrophobic spherical silica fine particles to be mixed with the carbon fibers will now be described in detail. The hydrophobic spherical silica microparticles used in the present invention are (A1) a step of obtaining hydrophilic spherical silica microparticles substantially composed of SiO units by hydrolyzing and condensing a tetrafunctional silane compound, a partial hydrolysis and condensation product thereof, or a combination thereof; (A2) R is applied to the surface of the hydrophilic spherical silica fine particles. 1 SiO 3 / 2Units (wherein R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms; (A3)R 2 3SiO 1 / 2 Units (wherein, each R 2 are the same or different and are substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms), The hydrophobic spherical silica particles have a particle diameter in the range of 0.005 to 0.3 μm, a particle size distribution D90 / D10 value of 3 or less, an average circularity of 0.8 to 1, and a hydrophobicity of 50 or more.
[0017] The hydrophobic spherical silica microparticles have a particle diameter of 0.005 to 0.3 μm, preferably 0.01 to 0.25 μm, and particularly preferably 0.03 to 0.20 μm. If the particle diameter is smaller than 0.005 μm, the particles are too small, so the flowability of the carbon fiber to the matrix resin may not increase, and the particles may not be dispersed well. If the particle diameter is larger than 0.3 μm, many particles may fall off even if they are attached to the carbon fiber, and good flowability and dispersibility in the resin may not be imparted, which is not preferable. In the present invention, the particle size distribution of the microparticles is measured by a dynamic light scattering method / laser Doppler method Nanotrac particle size distribution measuring device (manufactured by Microtrack Bell Co., Ltd., product name: NanotracWaveII-EX150), and the volume-based median diameter is taken as the particle diameter. The median diameter is the particle diameter corresponding to 50% of the cumulative distribution when the particle size distribution is expressed as a cumulative distribution.
[0018] The value of D90 / D10, which is an index of particle size distribution of the hydrophobic spherical silica microparticles, is 3 or less. Here, D10 and D90 are values obtained by measuring the particle size distribution, respectively. When measuring the particle size distribution of a powder, the particle size that is 10% cumulative from the small side is called D10, and the particle size that is 90% cumulative from the small side is called D90. Since this D90 / D10 is 3 or less, the particle size distribution of the hydrophobic spherical silica microparticles in the present invention is characterized by being sharp. Particles with such a sharp particle size distribution are preferable in that it is easy to control the dispersibility of carbon fibers. The above D90 / D10 is more preferably 2.9 or less.
[0019] The average circularity of the hydrophobic spherical silica microparticles is 0.8 to 1, and preferably 0.92 to 1. Here, "spherical" includes not only perfect spheres but also slightly distorted spheres. Such a "spherical" shape is evaluated by the circularity when the particle is projected two-dimensionally, and refers to a circularity in the range of 0.8 to 1. Here, the circularity is (perimeter of a circle equal to the particle area) / (particle perimeter). This circularity can be measured by image analysis of particle images obtained by an electron microscope or the like.
[0020] Furthermore, the hydrophobicity of the hydrophobic spherical silica microparticles is at least 50, and preferably at least 58. Here, the hydrophobicity is determined by a methanol titration test, and is a value expressed as the volume percentage of methanol in a mixture of methanol and water when silica microparticles added to water are wetted, with a larger value indicating a higher hydrophobicity and a smaller value indicating a higher hydrophilicity.
[0021] In step (A1), the hydrophilic spherical silica microparticles "consist essentially of SiO2 units" means that the microparticles are basically composed of SiO2 units, but are not composed only of the units, and have a large number of silanol groups at least on the surface as is generally known.In addition, in some cases, it means that the hydrolyzable groups (hydrocarbyloxy groups) derived from the raw material tetrafunctional silane compound and / or its partial hydrolysis condensation product may remain on the surface or inside of the microparticles in a small amount without being converted into silanol groups.
[0022] The hydrophobic spherical silica microparticles used in the present invention are prepared by subjecting the silica raw material (hydrophilic spherical silica microparticles) to a specific surface treatment, which is carried out on small-sized sol-gel silica obtained by hydrolysis of tetraalkoxysilane. When obtained as a powder, the particle size after surface treatment maintains the primary particle size of the silica raw material, is not aggregated, and has a small particle size, which can impart good fluidity and dispersibility to carbon fibers.
[0023] Small particle size silica precursor can be obtained with any particle size by changing the reaction conditions, such as using a tetraalkoxysilane having an alkoxy group with a small number of carbon atoms, using an alcohol with a small number of carbon atoms as the solvent, increasing the hydrolysis temperature, decreasing the concentration of the tetraalkoxysilane during hydrolysis, or decreasing the concentration of the hydrolysis catalyst.
[0024] The desired hydrophobic spherical silica particles can be obtained by subjecting this small particle size silica base material to a specific surface treatment as described above and in more detail below.
[0025] One method for producing hydrophobic spherical silica microparticles will now be described in detail.
[0026] <Method of producing hydrophobic spherical silica particles> The hydrophobic spherical silica microparticles used in the present invention are Step (A1): A step of synthesizing hydrophilic spherical silica microparticles; Step (A2): Surface treatment step using a trifunctional silane compound; Step (A3): Surface treatment step using a monofunctional silane compound Each step will be described below in order.
[0027] Step (A1): Synthesis of hydrophilic spherical silica particles Step (A1) is a step of obtaining hydrophilic spherical silica microparticles substantially composed of SiO2 units by hydrolyzing and condensing a tetrafunctional silane compound, its partial hydrolysis and condensation product, or a mixture thereof, and specifically, the following procedure is preferably carried out. First, the general formula (I): Si(OR 3 )4(I) (In the formula, each R 3 A tetrafunctional silane compound represented by the formula: (wherein each of the formulas is the same or different monovalent hydrocarbon group having 1 to 6 carbon atoms), its partial hydrolysis product, or a mixture of these, is hydrolyzed and condensed in a mixed solution of water and a hydrophilic organic solvent containing a basic substance to obtain a mixed solvent dispersion of hydrophilic spherical silica microparticles.
[0028] In the above general formula (I), R 3 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 3 Examples of the monovalent hydrocarbon group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, a propyl group, and a butyl group; and aryl groups such as a phenyl group. Of these, a methyl group, an ethyl group, a propyl group, or a butyl group is preferable, and a methyl group or an ethyl group is particularly preferable.
[0029] Examples of the tetrafunctional silane compound represented by the above general formula (I) include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane; and tetraphenoxysilane, preferably tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane, and particularly preferably tetramethoxysilane and tetraethoxysilane. Examples of the partial hydrolysis condensation product of the tetrafunctional silane compound represented by the general formula (I) include alkyl silicates such as methyl silicate and ethyl silicate.
[0030] The hydrophilic organic solvent is not particularly limited as long as it dissolves the tetrafunctional silane compound represented by the general formula (I), the partial hydrolysis condensation product thereof, and water, and examples thereof include alcohols; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and cellosolve acetate; ketones such as acetone and methyl ethyl ketone; ethers such as dioxane and tetrahydrofuran; and the like. Preferred are alcohols and cellosolves, and particularly preferred are alcohols. Examples of the alcohols include those represented by the general formula (V): R 5 OH (V) (In the formula, R 5 is a monovalent hydrocarbon group having 1 to 6 carbon atoms).
[0031] In the general formula (V) above, R 5 R is preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, particularly preferably 1 to 2 carbon atoms. 5Examples of the monovalent hydrocarbon group represented by the formula (V) include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl, preferably methyl, ethyl, propyl, and isopropyl, and more preferably methyl and ethyl. Examples of the alcohol represented by the formula (V) include methanol, ethanol, propanol, isopropanol, and butanol, and preferably methanol and ethanol. The particle size of the spherical silica microparticles produced increases with the number of carbon atoms of the alcohol. Therefore, methanol is preferred to obtain silica microparticles with a small particle size.
[0032] Examples of the basic substance include ammonia, dimethylamine, diethylamine, etc., preferably ammonia and diethylamine, and particularly preferably ammonia. A required amount of these basic substances may be dissolved in water, and the resulting aqueous solution (basic) may be mixed with the hydrophilic organic solvent. The amount of the basic substance used is preferably 0.01 to 2 mol, more preferably 0.02 to 0.5 mol, and particularly preferably 0.04 to 0.12 mol, per mol of the total of the hydrocarbyloxy groups of the tetrafunctional silane compound represented by the general formula (I) and / or its partial hydrolysis condensation product. In this case, the smaller the amount of the basic substance, the more the desired small-diameter silica particles can be obtained.
[0033] The amount of water used in the above hydrolysis and condensation is preferably 0.5 to 5 moles, more preferably 0.6 to 2 moles, and particularly preferably 0.7 to 1 mole, per mole of the total of hydrocarbyloxy groups in the tetrafunctional silane compound represented by formula (I) and / or its partial hydrolysis condensation product. The ratio of the above hydrophilic organic solvent to water (hydrophilic organic solvent / water) is preferably 0.5 to 10, more preferably 3 to 9, and particularly preferably 5 to 8, by mass. The greater the amount of the hydrophilic organic solvent, the more silica fine particles with the desired small particle size can be obtained.
[0034] The hydrolysis and condensation of the tetrafunctional silane compound represented by the general formula (I) can be carried out by a well-known method, that is, by adding the tetrafunctional silane compound represented by the general formula (I) to a mixture of a hydrophilic organic solvent containing a basic substance and water.
[0035] The concentration of the hydrophilic spherical silica fine particles in the mixed solvent dispersion obtained in step (A1) is generally 3 to 15% by mass, and preferably 5 to 10% by mass.
[0036] Step (A2): Surface treatment step using a trifunctional silane compound In step (A2), R is applied to the surface of the hydrophilic spherical silica fine particles obtained in step (A1). 1 SiO 3 / 2 Units (wherein R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms), and specifically, it is preferable to carry out the following procedure. The hydrophilic spherical silica microparticles obtained in the step (A1) are dispersed in a mixed solvent, and a compound represented by the general formula (II): R 1 Si(OR 4 )3(II) (In the formula, R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and each R 4 are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms), or a partial hydrolysis product thereof, or a mixture thereof, and the surface of the hydrophilic spherical silica fine particles is treated with the trifunctional silane compound represented by the formula (I) or (II), thereby forming a hydrophilic spherical silica fine particle having a hydrophilic group R on the surface of the hydrophilic spherical silica fine particles. 1 SiO 3 / 2 Units (R 1 as described above) to obtain a mixed solvent dispersion of the first hydrophobic spherical silica microparticles.
[0037] This step (A2) is essential for suppressing aggregation of the silica fine particles in the next concentration step. If aggregation cannot be suppressed, the individual particles of the resulting silica fine particles cannot maintain their primary particle size, and the fluidity imparting ability will be deteriorated.
[0038] In the above general formula (II), R 1 R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, preferably a monovalent hydrocarbon group having 1 to 3 carbon atoms, and particularly preferably a monovalent hydrocarbon group having 1 to 2 carbon atoms. 1 Examples of the monovalent hydrocarbon group represented by the formula (1) include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, butyl, and hexyl, preferably methyl, ethyl, n-propyl, or isopropyl, and more preferably methyl or ethyl. Some or all of the hydrogen atoms in these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, preferably fluorine atoms.
[0039] In the above general formula (II), R 4 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably 1 to 3 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 4 Examples of the monovalent hydrocarbon group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, a propyl group, and a butyl group, preferably a methyl group, an ethyl group, or a propyl group, and more preferably a methyl group or an ethyl group.
[0040] Examples of the trifunctional silane compound represented by the general formula (II) include unsubstituted or halogen-substituted trialkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, trifluoropropyltrimethoxysilane, and heptadecafluorodecyltrimethoxysilane, and preferably methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane, and more preferably methyltrimethoxysilane and methyltriethoxysilane, or partial hydrolysis and condensation products thereof.
[0041] The amount of the trifunctional silane compound represented by the general formula (II) added is 0.001 to 1 mol, preferably 0.01 to 0.1 mol, and particularly preferably 0.01 to 0.05 mol per mol of Si atom in the hydrophilic spherical silica microparticles used. If the amount added is less than 0.001 mol, the dispersibility of the resulting hydrophobic spherical silica microparticles is poor, so that the effect of imparting fluidity to the carbon fibers is not exhibited, and if it is more than 1 mol, aggregation of the silica microparticles may occur.
[0042] The concentration of the silica microparticles in the mixed solvent dispersion of the first hydrophobic spherical silica microparticles obtained here is usually preferably 3% by mass or more and less than 15% by mass, particularly preferably 5 to 10% by mass. If the concentration is too low, there is a disadvantage that the productivity decreases, and if it is too high, there is a risk of the silica microparticles agglomerating.
[0043] ·Concentration process The hydrophilic organic solvent and a part of the water may be removed from the thus obtained first hydrophobic spherical silica microparticle mixed solvent dispersion, and the mixture may be concentrated to obtain a first hydrophobic spherical silica microparticle mixed solvent concentrated dispersion. In this case, the hydrophobic organic solvent may be added in advance (before the concentration step) or during the concentration step. In this case, the hydrophobic solvent used is preferably a hydrocarbon-based or ketone-based solvent. Specifically, the solvent may be toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, etc., and methyl isobutyl ketone is preferred. Examples of the method for removing the hydrophilic organic solvent and a part of the water include distillation and distillation under reduced pressure. The obtained concentrated dispersion preferably has a silica microparticle concentration of 15 to 40% by mass, more preferably 20 to 35% by mass, and particularly preferably 25 to 30% by mass. If the silica microparticle concentration is lower than 15% by mass, the surface treatment in the subsequent step may not proceed smoothly, and if it is higher than 40% by mass, aggregation of the silica microparticles may occur.
[0044] The concentration step is also significant in that it prevents problems such as the silazane compound represented by general formula (III) and the monofunctional silane compound represented by general formula (IV), which are used as surface treatment agents in the next step (A3), reacting with alcohol or water to result in insufficient surface treatment, which then leads to aggregation during drying, causing the obtained silica powder to be unable to maintain its primary particle size and to have poor fluidity-imparting ability.
[0045] Step (A3): Surface treatment step using a monofunctional silane compound In step (A3), R is applied to the surface of the spherical silica fine particles obtained in step (A2). 2 3SiO 1 / 2 Units (wherein, each R 2 is the same or different, and is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 6 carbon atoms), and specifically, it is preferable to carry out the following procedure. The first hydrophobic spherical silica microparticles obtained in step (A2) are dispersed in a mixed solvent. General formula (III): R 23SiNHSiR 2 3(III) (In the formula, each R 2 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms. A silazane compound represented by the formula: General formula (IV): R 2 3SiX (IV) (In the formula, R 2 is as defined in general formula (III), and X is an OH group or a hydrolyzable group. or a mixture thereof, thereby treating the surface of the first hydrophobic spherical silica fine particles, and forming R 2 3SiO 1 / 2 Units (R 2 is defined as in general formula (III) to obtain second hydrophobic spherical silica particles. By the treatment in this step, the silanol groups remaining on the surface of the first hydrophobic spherical silica particles are triorganosilated to R 2 3SiO 1 / 2 Units are introduced onto the surface.
[0046] In the above general formulas (III) and (IV), R 2 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 2 Examples of the monovalent hydrocarbon group represented by the formula (1) include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, and butyl, preferably methyl, ethyl, or propyl, and particularly preferably methyl or ethyl. Some or all of the hydrogen atoms in these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, preferably fluorine.
[0047] In the above general formula (IV), examples of the hydrolyzable group represented by X include a chlorine atom, an alkoxy group, an amino group, and an acyloxy group, preferably an alkoxy group or an amino group, and particularly preferably an alkoxy group.
[0048] The silazane compound represented by general formula (III) may be, for example, hexamethyldisilazane, hexaethyldisilazane, etc., preferably hexamethyldisilazane. The monofunctional silane compound represented by general formula (IV) may be, for example, monosilanol compounds such as trimethylsilanol and triethylsilanol; monochlorosilanes such as trimethylchlorosilane and triethylchlorosilane; monoalkoxysilanes such as trimethylmethoxysilane and trimethylethoxysilane; monoaminosilanes such as trimethylsilyldimethylamine and trimethylsilyldiethylamine; monoacyloxysilanes such as trimethylacetoxysilane, preferably trimethylsilanol, trimethylmethoxysilane, or trimethylsilyldiethylamine, particularly preferably trimethylsilanol or trimethylmethoxysilane.
[0049] The amount of the silazane compound and / or functional silane compound used is 0.1 to 0.5 mol, preferably 0.2 to 0.4 mol, and particularly preferably 0.25 to 0.35 mol, per mol of Si atom in the hydrophilic spherical silica microparticles used. If the amount used is less than 0.1 mol, the dispersibility of the resulting hydrophobic spherical silica microparticles is poor, and the effect of imparting fluidity to the carbon fibers may not be achieved. If the amount used is more than 0.5 mol, it is economically disadvantageous.
[0050] The second hydrophobic spherical silica fine particles can be obtained as a powder by a conventional method such as drying under normal pressure or drying under reduced pressure, and can be used as the hydrophobic spherical silica fine particles for use in the present invention.
[0051] <Modified carbon fiber> (Process B) The modified carbon fiber of the present invention is a product obtained by mixing carbon fiber and the hydrophobic spherical silica microparticles, and adhering the hydrophobic spherical silica microparticles to the fiber surface and between fibers of the carbon fiber. The amount of the hydrophobic spherical silica microparticles used is preferably 0.01 to 20.0 mass% of the mass of the carbon fiber, more preferably 0.1 to 15.0 mass%, particularly 0.5 to 10.0 mass%. If this amount is less than 0.01 mass%, the flowability and dispersibility of the carbon fiber may not change, which is not preferable. Furthermore, if the amount added exceeds 20.0 mass%, it may be unfavorable in terms of cost. The modified carbon fiber is usually composed of carbon fiber and the hydrophobic spherical silica microparticles, but may optionally contain additives such as colorants, conductivity imparting agents, and coupling agents.
[0052] The carbon fibers and the hydrophobic spherical silica microparticles may be mixed in a known manner, and predetermined amounts of each component may be mixed uniformly using a Henschel mixer, a V-type blender, a ribbon blender, a Raikai mixer, a kneader mixer, a butterfly mixer, or a mixer or shaker with a conventional propeller stirrer. By such a mixing method, the hydrophobic spherical silica microparticles can easily enter the carbon fibers, untangle the fibers, and adhere well to the carbon fiber surface. In the manufacturing method of the present invention, the surface of the hydrophobic spherical silica microparticles is highly hydrophobized with trialkylsilyl groups by the compound represented by the above general formula (III) and / or (IV), so that the hydrophobic spherical silica microparticles adhere to the carbon fiber surface while repelling each other with a weak electrostatic force. It is presumed that the hydrophobic spherical silica microparticles adhere to the carbon fiber surface while spreading out, without agglomerating each other.
[0053] <Modified carbon fiber-containing thermoplastic resin composition> (Step C) Examples of the thermoplastic resins used in the present invention include polyolefin resins such as high-density polyethylene resin, low-density polyethylene resin, linear low-density polyethylene resin, very low-density polyethylene resin, polypropylene resin, polybutadiene resin, cyclic olefin resin, polymethylpentene resin, and ultra-high molecular weight polyethylene resin; polyamide resins such as nylon 4,6, nylon 6, nylon 6,6, nylon 6,10, nylon 6,12, nylon 12, nylon 6,T, nylon 9,T, and aromatic nylon resin; polystyrene resin, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-vinyl alcohol copolymer resin, ethylene-ethyl acrylate copolymer, acrylonitrile-styrene resin, acrylonitrile-chlorinated polystyrene-styrene copolymer resin, acrylonitrile-acrylic rubber-styrene copolymer resin, acrylonitrile-butadiene-styrene copolymer resin, acrylonitrile-EPDM-styrene copolymer resin, silicone rubber-acrylonitrile-styrene copolymer resin, cellulose-acetate-butyrate resin, cellulose acetate resin, methacrylate resin, cellulose acetate copolymer, cellulose acetate resin ... resin, ethylene-methyl methacrylate copolymer resin, ethylene-ethyl acrylate resin, vinyl chloride resin, chlorinated polyethylene resin, polytetrafluoroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin, tetrafluoroethylene-ethylene copolymer resin, polytrifluorochloroethylene resin, polyvinylidene fluoride resin, polyacetal resin, polybutylene terephthalate resin, polyethylene terephthalate resin, polyethylene naphthalate resin, amorphous copolyester resin, polycarbonate resin, modified polyphenylene ether resin, thermoplastic polyurethane elastomer, polyphenylene sulfide resin, polyether ether ketone resin, liquid crystal polymer, polytetrafluoroethylene resin, polyfluoroalkoxy resin, polyetherimide resin, polyketone resin, thermoplastic polyimide resin, polyamide imide resin, polyarylate resin, polysulfone resin, polyethersulfone resin, biodegradable resin, biomass resin, etc., but are not limited to these. In addition, two or more of these resins may be copolymerized or mixed.
[0054] Among these, at least one resin selected from the group consisting of polyolefin resins, polycarbonate resins, polyamide resins, and polyphenylene sulfide resins is preferred.
[0055] The modified carbon fiber-containing thermoplastic resin composition obtained by the production method of the present invention may contain suitable additives, such as oxidation stabilizers, weather stabilizers, antistatic agents, dyes, pigments, dispersants, coupling agents, etc., as necessary within the range that does not impair the effects of the present invention.
[0056] The production of the modified carbon fiber-containing thermoplastic resin composition in the present invention is not particularly limited. For example, the above-mentioned thermoplastic resin, the above-mentioned modified carbon fiber, and further various additives and colorants, etc. are added as necessary, mixed with a Henschel mixer, tumbler, disperser, etc., and mixed and melt-kneaded and dispersed with a batch mixer such as a kneader, roll mill, super mixer, Henschel mixer, Shugi mixer, vertical granulator, high-speed mixer, Farmatrix, ball mill, steel mill, sand mill, vibration mill, attritor, or Banbury mixer, twin-screw extruder, single-screw extruder, or rotor-type twin-screw kneader, etc., to obtain a modified carbon fiber-containing thermoplastic resin composition in the form of pellets, powder, granules, beads, etc.
[0057] The modified carbon fiber-containing thermoplastic resin composition obtained by the manufacturing method of the present invention may be a master batch containing a relatively high concentration of modified carbon fiber and being diluted with the resin to be molded (base resin) during molding, or it may be a compound containing a relatively low concentration of modified carbon fiber and being used for molding with almost the same composition without diluting the resin to be molded. The amount of the modified carbon fiber added to the modified carbon fiber-containing thermoplastic resin composition is 0.5 to 40 parts by mass, and preferably 2.0 to 30 parts by mass, per 100 parts by mass of thermoplastic resin, from the viewpoints of the fluidity of the modified carbon fiber in the resin and the mechanical strength of the resulting resin composition.
[0058] The modified carbon fiber-containing thermoplastic resin composition obtained by the production method of the present invention can be used to obtain a molded article by a heat molding method such as extrusion molding, injection molding, or blow molding. EXAMPLES
[0059] The present invention will be specifically described below using examples and comparative examples. Note that the following examples do not limit the present invention in any way.
[0060] [Synthesis of hydrophobic spherical silica particles] <Synthesis Example 1> Step (A1): Synthesis of hydrophilic spherical silica particles 989.5g of methanol, 135.5g of water, and 66.5g of 28% aqueous ammonia were mixed in a 3-liter glass reactor equipped with a stirrer, a dropping funnel, and a thermometer. The solution was adjusted to 38°C, and 436.5g (2.87 moles) of tetramethoxysilane was dropped into the solution over 6 hours while stirring. After the dropping was completed, stirring was continued for another 0.5 hours to carry out hydrolysis, and a suspension of hydrophilic spherical silica particles was obtained.
[0061] Step (A2): Surface treatment step using a trifunctional silane compound To the suspension obtained above, 4.4 g (0.03 mol) of methyltrimethoxysilane was added dropwise at room temperature over 0.5 hours, and stirring was continued for 12 hours after the addition to hydrophobize the surface of the silica particles, thereby obtaining a dispersion of hydrophobic spherical silica particles.
[0062] Next, an ester adaptor and a cooling tube were attached to the glass reactor, and the dispersion obtained in the previous step was heated to 60-70°C to distill off 1021 g of the mixture of methanol and water, to obtain a mixed solvent concentrated dispersion of hydrophobic spherical silica microparticles. At this time, the content of hydrophobic spherical silica microparticles in the concentrated dispersion was 28 mass%.
[0063] Step (A3): Surface treatment step using a monofunctional silane compound To the concentrated dispersion obtained in the previous step, 138.4 g (0.86 mol) of hexamethyldisilazane was added at room temperature, and the dispersion was heated to 50-60° C. and reacted for 9 hours to trimethylsilylate the silica particles in the dispersion. The solvent in the dispersion was then distilled off at 130° C. under reduced pressure (6650 Pa) to obtain 185 g of hydrophobic spherical silica particles (1).
[0064] The hydrophilic spherical silica microparticles obtained in step (A1) were measured according to the following measurement method 1. The hydrophobic spherical silica microparticles obtained through each of the above steps (A1) to (A3) were measured according to the following measurement methods 1 to 4. The obtained results are shown in Table 1.
[0065] [Measurement method 1~4] 1. Measurement of particle size of hydrophilic spherical silica microparticles obtained in step (A1) Silica microparticle suspension was added to methanol so that silica microparticles were 0.5% by mass, and the microparticles were dispersed by applying ultrasonic waves for 10 minutes. The particle size distribution of the microparticles thus treated was measured by a dynamic light scattering method / laser Doppler method nanotrack particle size distribution measuring device (manufactured by Microtrack Bell Co., Ltd., product name: NanotracWaveII-EX150), and the volume-based median diameter was taken as the particle size. The median diameter is the particle size corresponding to the cumulative 50% when the particle size distribution is expressed as a cumulative distribution.
[0066] 2. Measurement of particle size and particle size distribution D90 / D10 of the hydrophobic spherical silica microparticles obtained in step (A3) Silica fine particles were added to methanol to a concentration of 0.5% by mass, and the fine particles were dispersed by applying ultrasonic waves for 10 minutes. The particle size distribution of the fine particles thus treated was measured using a dynamic light scattering / laser Doppler method Nanotrac particle size distribution measuring device (manufactured by Microtrack Bell Co., Ltd., product name: NanotracWaveII-EX150), and the volume-based median diameter was taken as the particle size. The particle size distribution D90 / D10 was measured by setting the particle size at which the cumulative total was 10% from the small side in the distribution when the particle size was measured as D10, and the particle size at which the cumulative total was 90% from the small side as D90, and calculating D90 / D10 from the measured values.
[0067] 3. Shape measurement of hydrophobic spherical silica particles The shape was confirmed by observation using an electron microscope (Hitachi, product name: S-4700, magnification: 100,000 times). "Spherical" includes not only perfect spheres but also slightly distorted spheres. The shape of such particles is evaluated by the circularity when the particles are projected two-dimensionally, and the circularity is in the range of 0.8 to 1. Here, the circularity is calculated by dividing the perimeter of a circle equal to the particle area by the perimeter of the particle.
[0068] 4. Measurement of hydrophobicity of hydrophobic spherical silica particles The hydrophobicity was measured by a methanol titration test. Specifically, methanol was added dropwise from a burette to the silica particle mixture while stirring it until the entire amount of 0.2 g of silica particles added to 50 ml of water was wetted, and the value expressed by the volume percentage of methanol in the mixture of methanol and water at the end point was taken as the hydrophobicity.
[0069] <Synthesis Example 2> In the same manner as in Synthesis Example 1, except that the amounts of methanol, water, and 28% aqueous ammonia in step (A1) were changed to 1045.7 g of methanol, 112.6 g of water, and 33.2 g of 28% aqueous ammonia, and the reaction temperature was changed to 35° C., 185 g of hydrophobic spherical silica microparticles (2) were obtained. Measurements were performed using these hydrophobic spherical silica microparticles in the same manner as in Synthesis Example 1. The results are shown in Table 1.
[0070] <Synthesis Example 3> ·Process (A1): In a 3-liter glass reactor equipped with a stirrer, a dropping funnel and a thermometer, 623.7 g of methanol, 41.4 g of water and 49.8 g of 28% aqueous ammonia were added and mixed. The solution was adjusted to 35°C, and while stirring, 1163.7 g of tetramethoxysilane and 418.1 g of 5.4% aqueous ammonia were added dropwise to the solution, the former over 6 hours and the latter over 4 hours. After the dropping of tetramethoxysilane, stirring was continued for 0.5 hours to carry out hydrolysis, and a suspension of silica fine particles was obtained.
[0071] ·Process (A2): To the suspension thus obtained, 11.6 g of methyltrimethoxysilane (equivalent to 0.01 molar ratio relative to tetramethoxysilane) was added dropwise at room temperature over 0.5 hours, and the mixture was stirred for 12 hours after the addition to treat the surfaces of the silica fine particles.
[0072] An ester adapter and a cooling tube were attached to the glass reactor, and 1,440 g of methyl isobutyl ketone was added to the dispersion containing the above-mentioned surface-treated silica fine particles. The mixture was then heated to 80 to 110°C, and the methanol water was distilled off over 7 hours.
[0073] ·Process (A3): To the dispersion thus obtained, 357.6 g of hexamethyldisilazane was added at room temperature, and the mixture was heated to 120° C. and reacted for 3 hours to trimethylsilylate the silica microparticles. The solvent was then distilled off under reduced pressure to obtain 473 g of hydrophobic spherical silica microparticles (3).
[0074] The silica fine particles (3) thus obtained were subjected to the same measurements as in Synthesis Example 1. The results are shown in Table 1.
[0075] <Synthesis Example 4> In the synthesis of silica microparticles, each step was carried out in the same manner as in Synthesis Example 3, except that the hydrolysis temperature of tetramethoxysilane was 20°C instead of 35°C, and 464 g of hydrophobic spherical silica microparticles (4) was obtained. Using these hydrophobic spherical silica microparticles (4), the same measurements as in Synthesis Example 1 were carried out. The results are shown in Table 1.
[0076] <Comparative Synthesis Example 1> A 0.3-liter glass reactor equipped with a stirrer and a thermometer was charged with 100 g of deflagration silica (trade name: SOC1, manufactured by Admatechs Co., Ltd.), 1 g of pure water was added with stirring, and the reactor was sealed and further stirred at 60°C for 10 hours. After cooling to room temperature, 2 g of hexamethyldisilazane was added with stirring, and the reactor was sealed and further stirred for 24 hours. The temperature was raised to 120°C, and the remaining raw materials and the generated ammonia were removed while passing nitrogen gas through the reactor, to obtain 100 g of hydrophobic spherical silica microparticles (5).
[0077] The obtained silica fine particles (5) were subjected to the same measurements as in Synthesis Example 1. The results are shown in Table 1.
[0078] <Comparative Synthesis Example 2> A 0.3-liter glass reactor equipped with a stirrer and a thermometer was charged with 100 g of deflagration silica (trade name: SOC1, manufactured by Admatechs Co., Ltd.), 1 g of pure water was added under stirring, and the reactor was sealed and further stirred at 60° C. for 10 hours. Then, after cooling to room temperature, 1 g of methyltrimethoxysilane was added under stirring, and the reactor was sealed and further stirred for 24 hours. Next, 2 g of hexamethyldisilazane was added under stirring, and the reactor was sealed and further stirred for 24 hours. The temperature was raised to 120° C., and the remaining raw materials and the generated ammonia were removed while passing nitrogen gas through the reactor, to obtain 101 g of hydrophobic spherical silica microparticles (6). The obtained silica microparticles (6) were subjected to the same measurements as in Synthesis Example 1. The results are shown in Table 1.
[0079] [Table 1] <Note> 1) Particle diameter of the hydrophilic spherical silica microparticles in the dispersion obtained in step (A1) 2) Particle size of the final hydrophobic spherical silica microparticles
[0080] [Production of modified carbon fibers] <Production Examples 1 to 5, Comparative Production Examples 1 to 5> The above-mentioned hydrophobic spherical silica microparticles (1) to (6) and cut carbon fiber bundles (TORAYCA T-700SC-12000 manufactured by Toray Industries, Inc., fineness tex: 800 g / 1,000 m, tensile strength: 4,900 MPa, tensile modulus: 230 GPa) were added to a plastic container in the amounts shown in Table 2, and mixed with a Strong Shaker SR-2DS shaker manufactured by TAITEC Co., Ltd. at a shaking speed of 250 r / min for 10 minutes. After that, the mixture was heated at 50°C for 30 minutes and further pressed at 150°C, 50 kN, and 3 minutes to obtain modified carbon fibers.
[0081] <Production Examples 6 to 10, Comparative Production Examples 6 to 10> Modified carbon fibers were produced in the same manner as in Production Examples 1 to 5 and Comparative Production Examples 1 to 5, except that carbon fiber bundles from which the following sizing agent had been removed were used as the carbon fiber bundles. The amounts of each hydrophobic spherical silica microparticle and carbon fiber added are shown in Table 3. [Preparation of carbon fiber bundles with sizing agent removed] A 2-liter glass reactor equipped with a thermometer was charged with 96 parts by mass of carbon fiber bundle TORAYCA T-700SC-12000 and 500 parts by mass of methyl ethyl ketone, and the mixture was heated under reflux for 1 hour. The mixture was then decanted, washed with cold methyl ethyl ketone, and dried under heating and reduced pressure to obtain a carbon fiber bundle from which the sizing agent had been removed.
[0082] [Table 2]
[0083] [Table 3]
[0084] The modified carbon fiber bundle obtained in Production Example 2 was cooled with liquid nitrogen, and the surface was observed using an electron microscope (manufactured by Hitachi, Ltd., product name: S-4700 type) with the results shown in Figure 1. It was found that hydrophobic spherical silica particles were uniformly present on the carbon fiber surface.
[0085] [Production of modified carbon fiber-containing thermoplastic resin composition] <Example 1> Polypropylene (PP) resin (SunAllomer Corporation PY-6) was formed into a sheet of approximately 100 μm thickness, and the modified carbon fiber obtained in Production Example 1 was sandwiched between the sheets as shown in FIG. 2. The ratio of the modified carbon fiber was 10 parts by mass per 100 parts by mass of polypropylene resin. After preheating at 180° C. for 2 minutes, the sheets were press molded at 180° C. and 40 kN for 3 minutes. The molded sheet was cut as shown in FIG. 3 to prepare a fragmentation test piece, and its strength was measured using an autograph. The critical breaking length and interfacial shear strength of the fiber were calculated based on the measurement results according to FIG. 4, and the results are shown in Table 4.
[0086] <Examples 2 to 10 and Comparative Examples 1 to 10> In Example 1, fragmentation test pieces were prepared in the same manner as in Example 1, except that the modified carbon fiber obtained in Production Example 1 was changed to that obtained in Production Examples 2 to 10 and Comparative Production Examples 1 to 10, respectively, and measurements were performed. The results are shown in Table 4.
[0087] <Example 11> Nylon 6 (PA6) resin (Amilan CM-1006, manufactured by Toray Industries, Inc.) was formed into a sheet of approximately 100 μm thickness, and the modified carbon fiber obtained in Production Example 1 was sandwiched between the sheets as shown in FIG. 2. The sheets were preheated at 240°C for 2 minutes, and then press molded at 240°C and 40 kN for 3 minutes. The sheets were cut as shown in FIG. 3 to prepare fragmentation test pieces, and their strength was measured using an autograph. The critical breaking length and interfacial shear strength of the fibers were calculated based on the measurement results according to FIG. 4, and the results are shown in Table 5.
[0088] <Examples 12 to 20, Comparative Examples 11 to 20> In Example 11, fragmentation test pieces were prepared in the same manner as in Example 11, except that the modified carbon fiber obtained in Production Example 1 was changed to that obtained in Production Examples 2 to 10 and Comparative Production Examples 1 to 10, respectively, and measurements were performed. The results are shown in Table 5.
[0089] [Table 4]
[0090] [Table 5]
[0091] As shown in Tables 4 and 5, the modified carbon fiber-containing thermoplastic resin compositions of Examples 1 to 10 and Examples 11 to 20 had superior interfacial shear strength compared to those of Comparative Examples 1 to 10 and Comparative Examples 11 to 20, demonstrating excellent interfacial adhesion between the modified carbon fiber and the thermoplastic resin.
[0092] <Examples 21 to 24, Comparative Examples 21 to 22> A twin-screw extruder (L / D=45, screw diameter 20 mm, same direction rotation, injection section temperature 220°C, mixing temperature 250°C, rotation speed 150 rpm) was used to mix, dissolve, and disperse each component in the blending ratio shown in Table 6 to produce a kneaded strand. This strand was processed into pellets using a pelletizer, and molded into an ISO dumbbell using an injection molding machine (injection time 2 seconds, back pressure 5 MPa, dwell pressure 20 MPa, dwell time 10 seconds, cylinder temperature 250°C, mold temperature 60°C). The bending strength, elongation, and IZOD impact strength of the dumbbell were measured, and the results are shown in Table 7.
[0093] [Table 6] Thermoplastic resin: Amilan CM-1006 manufactured by Toray Industries, Inc. Carbon fiber A: Toray Industries, Inc., Torayca T008-006 (containing sizing agent, fiber length 6 mm) Carbon fiber B: SIGRAFIL C T50-4.4 / 255-UN manufactured by SGL Carbon (no sizing agent, fiber length 6 mm)
[0094] [Table 7]
[0095] As shown in Table 7, the molded articles of Examples 21 to 24 were superior in mechanical strength to those of Comparative Examples 21 and 22. [Explanation of symbols]
[0096] 1 Molded Sheet 2. Fragmentation test specimen 10 Modified carbon fiber 20 Thermoplastic resin sheet
Claims
1. (A1) A tetrafunctional silane compound, a partial hydrolysis and condensation product thereof, or a mixture thereof is subjected to hydrolysis and condensation to substantially convert SiO 2 obtaining hydrophilic spherical silica microparticles consisting of units; (A2) The surface of the hydrophilic spherical silica fine particles is provided with R 1 SiO 3 / 2 Units (wherein R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms; (A3) The surface of the spherical silica fine particles obtained in the step (A2) is provided with R 2 3 SiO 1 / 2 Units (wherein each R 2 are the same or different and are substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms; A step A of producing hydrophobic spherical silica microparticles having a particle diameter in the range of 0.005 to 0.3 μm, a particle size distribution D90 / D10 value of 3 or less, an average circularity of 0.8 to 1, and a hydrophobicity of 50 or more by a method comprising the steps of: A step of mixing the hydrophobic spherical silica microparticles obtained in the step A and carbon fibers having a length of 0.3 to 10 mm into a thermoplastic resin. The present invention relates to a method for producing a modified carbon fiber-containing thermoplastic resin composition having the above formula, wherein the amount of hydrophobic spherical silica microparticles is at least 0.01% by mass relative to the mass of the carbon fiber, and the total amount of the hydrophobic spherical silica microparticles and the carbon fiber is 0.5 to 40 parts by mass relative to 100 parts by mass of the thermoplastic resin.
2. The method for producing the hydrophobic spherical silica microparticles comprises: (A1) General formula (I): Si(OR 3 ) 4 (I) (In the formula, each R 3 are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms), a partial hydrolysis product thereof, or a mixture thereof is hydrolyzed and condensed in a mixture of a hydrophilic organic solvent and water in the presence of a basic substance to obtain a tetrafunctional silane compound represented by the formula (I) or (II), which is substantially the same or different, and which is substantially the same as the tetrafunctional silane compound represented by the formula (I), 2 obtaining a mixed solvent dispersion of hydrophilic spherical silica microparticles comprising the units, (A2) The obtained hydrophilic spherical silica microparticles are dispersed in a mixed solvent, and a compound represented by the general formula (II): R 1 Si (OR 4 ) 3 (II) (In the formula, R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and each R 4 are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms), a partial hydrolysis product thereof, or a mixture thereof is added to treat the surface of the hydrophilic spherical silica fine particles, thereby forming a layer of R on the surface of the hydrophilic spherical silica fine particles. 1 SiO 3 / 2 Unit (R 1 is as described above) to obtain a first dispersion of hydrophobic spherical silica microparticles in the mixed solvent, (A3) The obtained first hydrophobic spherical silica microparticles are dispersed in a mixed solvent. General formula (III): R 2 3 SiNHSiR 2 3 (III) (In the formula, each R 2 are the same or different, substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms. A silazane compound represented by the formula: General formula (IV): R 2 3 SiX (IV) (In the formula, R 2 is as defined in general formula (III), and X is an OH group or a hydrolyzable group, Alternatively, a mixture of these is added to treat the surface of the first hydrophobic spherical silica fine particles, thereby forming R 2 3 SiO 1 / 2 Unit (R 2 is as defined in general formula (III)) to obtain second hydrophobic spherical silica microparticles, A method for producing the modified carbon fiber-containing thermoplastic resin composition according to claim 1.
3. The method for producing a modified carbon fiber-containing thermoplastic resin composition according to claim 1 or 2, wherein the amount of hydrophobic spherical silica microparticles is in the range of 0.01 to 20.0 mass% relative to the carbon fiber.
4. The thermoplastic resin is at least one resin selected from the group consisting of polyolefin resins, polycarbonate resins, polyamide resins and polyphenylene sulfide resins. A method for producing a modified carbon fiber-containing thermoplastic resin composition according to any one of claims 1 to 3.
5. A method for producing a molded body, comprising obtaining a modified carbon fiber-containing thermoplastic resin composition by the method according to any one of claims 1 to 4, and hot-molding the obtained modified carbon fiber-containing thermoplastic resin composition.
Citation Information
Patent Citations
Preparation method of carbon fiber and silicon dioxide nanosphere synergically filled ultra-high molecular weight polyethylene wear-resistant material
CN107663328A
Manufacturing method of fine carbon fiber-containing resin composition
JP2006282843A
Resin particle, and method for manufacturing the same
JP2012149190A
Propylene-based resin composition, and molded article of the same
JP2014028884A
Carbon nanotube composition and resin composition and molding using the same
JP2014167050A